Electromagnetic sounding of the Earth's interior - Spichak, V. V. (Viacheslav Valentinovich) (Methods in geochemistry and geophysics, 2007)
Based on lectures given in the First Russian School-Seminar on electromagnetic soundings of the Earth held in Moscow on 15th November, 2003, this book acquaints scientists and technologists with the latest achievements in theory, techniques and practical applications of the methods of electromagnetic sounding. This three part text covers the methods considered for Earth electromagnetic sounding on a global, regional, and local scale; modern methods for solving forward and inverse problems of geoelectrics, particularily contemporary approaches to the EM data modeling and interpretation in the class of three-dimensional models; and the results of regional EM on-land and sea soundings *Presents theoretical and methodological findings, as well as examples of applications of recently developed algorithms and software in solving practical problems *Describes the practical importance of electromagnetic data through enabling discussions on a construction of a closed technological cycle, processing, analysis and three-dimensional interpretation *Updates current findings in the field, especially with MT, magnetovariational and seismo-electriccal methods and the practice of 3D interpretaions.